1969
DOI: 10.25100/iyc.v19i2.5300
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de las condiciones óptimas para la obtención de un fertilizante fosfatado a partir de la roca fosfórica cubana

Abstract: Con la finalidad de lograr la seguridad alimentaria en el país, es necesario intensificar de manera sostenible la producción de fertilizantes para obtener incrementos de productividad y generar ganancias económicas, potenciando el uso de materias primas nacionales para disminuir las importaciones. Es por ello que, en este trabajo se realizó el estudio de la determinación de las condiciones óptimas del proceso de obtención de Superfosfato Sencillo (SFS) a escala de laboratorio, a partir de la roca fosfórica y e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, when comparing the solubility of samples M1 to M16, we found that all samples meet high solubility, while the assimilable phosphorus (an extractable fraction with weak acids) shown in Table 12, is low compared to sample superphosphate from the Cuban phosphoric rock (12.28 wt. % P 2 O 5 ) [29]. However, the Colombian Agricultural Institute (ICA in Spanish) indicates that the minimum acceptable contents for solid fertilizers (NPK) for soil application must be at least 3.0 wt.…”
Section: Analysis Of Assimilable Phosphorus and Solubility Index By U...mentioning
confidence: 99%
“…Therefore, when comparing the solubility of samples M1 to M16, we found that all samples meet high solubility, while the assimilable phosphorus (an extractable fraction with weak acids) shown in Table 12, is low compared to sample superphosphate from the Cuban phosphoric rock (12.28 wt. % P 2 O 5 ) [29]. However, the Colombian Agricultural Institute (ICA in Spanish) indicates that the minimum acceptable contents for solid fertilizers (NPK) for soil application must be at least 3.0 wt.…”
Section: Analysis Of Assimilable Phosphorus and Solubility Index By U...mentioning
confidence: 99%